Lectins from the Red Marine Algal SpeciesBryothamnion seaforthii and Bryothamnion triquetrum as Tools to Differentiate Human Colon Carcinoma Cells. (9th November 2009) - Pinto, Vicente P. T.; Debray, Henri; Dus, Danuta; Teixeira, Edson H.; de Oliveira, Taianá Maia; Carneiro, Victor Alves; Teixeira, Alrieta H.; Filho, Gerardo C.; Nagano, Celso S.; Nascimento, Kyria S.; Sampaio, Alexandre H.; Cavada, Benildo S.
Abstract : The carbohydrate-binding activity of the algal lectins from the closely related red marine algal species Bryothamnion triquetrum (BTL) and Bryothamnion seaforthii (BSL) was used to differentiate human colon carcinoma cell variants with respect to their cell membrane glyco-receptors. These lectins interacted with the cells tested in a dose-dependent manner. Moreover, the fluorescence spectra of both lectins clearly differentiated the cells used as shown by FACS profiles. Furthermore, as observed by confocal microscopy, BTL and BSL bound to cell surface glycoproteins underwent intense internalization, which makes them possible tools in targeting strategies.